Wealth, labour income, stock returns and government bond yields, and financial stress in the euro area - Sousa, Ricardo M. (2011)
I show that when the ratio of asset wealth to human wealth falls, investors become more exposed to idiosyncratic shocks and demand higher stock and government bond risk premia. I find that the residuals from the cointegrating vector among asset wealth and labour income, wy, predict both future stock and bond returns in the Euro Area. Consequently, it can be used to track time-variation in risk premium. The results are robust to the inclusion of control variables and vis-a-vis other benchmark models. Finally, I show that, conditioning the predictive ability of wy on the financial stress conditions allows one to track better future time-variation in risk premium. Moreover, when financial stress increases, investors perceive a larger risk for both stocks and government bonds.